PENERAPAN TEKNIK TOTAL TASK PRESENTATION UNTUK MENINGKATKAN KETERAMPILAN BUANG AIR KECIL PADA ANAK DENGAN DISABILITAS INTELEKTUAL MODERAT - Utami, Aryani Rahmah; Tedjasaputra, Mayke S. (Faculty of Psychology, Diponegoro University, 2018)
Children with intellectual disability (ID) have deficit in their adaptive functions, such as self-care in practical domain. The skill of self-care in moderate ID children can develop after being trained, although it takes a long time. One of skills that can be developed is urination skill. Urination skill is important to teach on children with ID so they can maintain their genital organs health independently. Therefore, interventions related to urination skill using behavior modification program with total task presentation technique are required. The purpose of this research is to evaluate the effectiveness of total task presentation technique to increase urination skill on child with moderate ID. This study used a single case subject A-B design that used to find changes in scores by comparing behavior observation data of participant’s urination skill and make a data analysis. Participant in this study was a 10 years old boy who has deficit in urination skill. After the implementation of the intervention program in 16 sessions for 14 days with 81 trials, it was found that the total task presentation technique is effective to improve urination skill on a child with moderate ID. The participants has been able to take control the entire range of urinating behavior (22 chain of behaviors) independently. Previously, the child could only controlled the nine chain of behaviors independently.